2021
DOI: 10.1016/s2213-2600(21)00099-0
|View full text |Cite
|
Sign up to set email alerts
|

Sarilumab in patients admitted to hospital with severe or critical COVID-19: a randomised, double-blind, placebo-controlled, phase 3 trial

Abstract: Background Elevated proinflammatory cytokines are associated with greater COVID-19 severity. We aimed to assess safety and efficacy of sarilumab, an interleukin-6 receptor inhibitor, in patients with severe (requiring supplemental oxygen by nasal cannula or face mask) or critical (requiring greater supplemental oxygen, mechanical ventilation, or extracorporeal support) COVID-19. Methods We did a 60-day, randomised, double-blind, placebo-controlled, multinational phase 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
174
4
10

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 217 publications
(190 citation statements)
references
References 28 publications
2
174
4
10
Order By: Relevance
“…Some patients were included in treatment trials [ 21 ]. Antibiotic therapy was withheld unless there were signs of bacterial infection (i.e., procalcitonin concentration in the serum >1 ng/mL, positive results on microbiological testing).…”
Section: Methodsmentioning
confidence: 99%
“…Some patients were included in treatment trials [ 21 ]. Antibiotic therapy was withheld unless there were signs of bacterial infection (i.e., procalcitonin concentration in the serum >1 ng/mL, positive results on microbiological testing).…”
Section: Methodsmentioning
confidence: 99%
“…In an open label cohort study published by Emanuel Della-Torre et al, it was shown that sarilumab was associated with better recovery in Covid patients with minimal symptoms, but was not a promising option for severe illness. 65 There were also other trials in conjecture with this finding. 66…”
Section: Sarilumabmentioning
confidence: 65%
“…A randomized, double-blind, placebo-controlled, phase three trial of sarilumab in patients admitted to Hospital with severe or critical COVID-19 was studied. Their result shows that the sarilumab efficacy is poor in patients admitted to Hospital with COVID-19 and receiving supplemental oxygen ( Lescure et al, 2021 ).…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%